Structural and histochemical attributes of secretory ducts and cavities in leaves of four species of Calophyllaceae J. Agardh in Amazonian savannas. (6th September 2021) - Pessoa, M. J. G.; Pireda, S.; Simioni, P.; Bautz, N.; Da Cunha, M.
Abstract: This study represents an important contribution to the structural, histochemical and biological understanding of ducts and cavities in leaves of four species of Calophyllaceae that occur in Amazonian savannas. Samples of adult leaves were processed using light, scanning and transmission electron microscopy, as per usual methods for plant anatomy. In paradermal sections, the lumina of ducts are elongated while those of cavities are short. Ducts occur exclusively in the central rib and are abundant in Kielmeyera rubriflora Cambess and Kielmeyera coriacea Mart. and Zucc and larger than in Calophyllum brasiliense Cambess and Caraipa densifolia Mart. In mesophyll, the type of secretory structure and distribution pattern of the ducts and cavities are distinct. In most species, the secreted metabolites are similar and consist of phenolic compounds, lipids, essential oils with oleoresins, mucilage, neutral polysaccharides, proteins and alkaloids, except in K. coriacea, which does not contain oleoresin. The secretion is probably synthesized by mitochondria, rough endoplasmic reticulum, ribosomes and dictyosomes and is externalized toward the lumen by granulocrine and eccrine processes. In addition to being of diagnostic value for species identification, the attributes of the lumen shape, type of secretory structure, distribution pattern, identified metabolites and secretion mechanism are important for understanding the biological roles of ducts and cavities. The identified metabolites reveal a capacity for adaptation, resistance and protection from the action of herbivores and pathogens, and in water retention. Abstract : The presence of ducts and cavities in the leaves shows that the plants adapt to biotic and abiotic factors.